Analysis of survival at cardiac arrest in events occurred in work environments in the territory served by an operations center of the 118 of Tuscany - Marino, Riccardo; Bertocci, Nicola; Bernabei, Micaela; Bonotti, Alessandra; Mignani, Aldo; Fallahi, Poupak; Perretta, Salvio; Monopoli, Giulia; Cristaudo, Alfonso; Foddis, Rudy (La Medicina del Lavoro, 2020)
Background: Every year in Italy and all around the world, cardiac arrest hits almost 1 person every 1000 people; a great deal of these events is likely to strike people outside their private houses. Objectives: Analyzing a cohort of cardiac arrest events occurred in various public- and work-places across a territorial area concerning an Emergency Unit related to the national emergency number (118) and assessing the efficacy of a first-aid intervention and the usage of a defibrillator while handling an acute cardiac event. Methods: We analyzed data of 32 sanitary interventions on cardiac arrest events occurred from January 2015 to June 2018 across USL Toscana Centro – Pistoia and Empoli’s territory. Results: The acute cardiac event occurred in a “strictly speaking workplace” in 28.2% of cases, and in 18.7% during work activity. An AED was present for immediate cardiac arrest treatment in 15.6% of cases with a survival rate of 100% (n=5/5) (p=0.04); in 84.4% of cases the AED was available only after the arrival of national emergency rescuers and the relative survival rate was 40.74% (n=11/27). Regarding cardiopulmonary resuscitation, the survival rate appears to be higher (55.5% Vs 42.8%) when it was started by witnesses. Conclusions: The results of this study suggest that early defibrillation provided by work-related First Aid Emergency Procedure, may be a primary aid and a desirable standard to improve both workers’ and private citizens’ survival rate after cardiac arrest.